Digital Marketing Training for Fishball MSMEs Group in Malingping District, Lebak Regency, Banten - Galih Ginanjar Saputra; Lina Affifatusholihah; Adih Supriadi; Edy Arisondha; Titis Nistia Sari; Firli Agusetiawan Shavab; Lukmanul Hakim Aziz (EQUATOR SINAR AKADEMIA, 2022)
This activity aims to help solve the problems faced by the Malingping Fishball MSME group. During pandemics, the number of sales decreased. This is a problem that must be solved. Troubleshooting is done through the interview method for the fishball MSME group. Next, the team determined the solutions and things needed by the fish ball MSME group. The method of implementing the activities is carried out using a community development model approach, which is provided in the form of training and assistance related to marketing techniques, namely in the form of digital marketing according to the needs of the fish ball MSME group. This activity is expected to help fishball SMEs expand their marketing network. The results show that this empowerment activity can be well received and the participants are considered ready to adapt to digitalization. Even so, there is an evaluation that the development of this program must be carried out on an ongoing basis because there are still some participants who need further direction and guidance.